Isolamento e caracterização de proteínas foliares da Ilex paraguariensis St. Hil. (erva mate) - Pereira, Danieli Hofmann (Universidade do Vale do Rio dos Sinos, 2015)
The Ilex paraguariensis is a plant from Aquifoliaceae family, native from subtropical South America, consumed and produced on a large scale in the southern regions of Brazil. The interest in the plant is increasing as studies are developed showing many benefits of Ilex paraguariensis. Most of these studies associate the antioxidant activity with its phenolic composition. However, since studies with other plant sources have also correlated the antioxidant properties with proteinaceous bioactive compounds it is important the evaluation and characterization of the Ilex paraguariensis proteins leaves, since bioactive compounds can be used as supplements for health or functional ingredients. In this context, the aim of this study was to characterize the foliar proteins from Ilex paraguariensis. Therefore, the leaves have gone through different extraction processes and fractionation. Initially, the plant material was homogenized with 50 mM Tris HCl pH 8, 1 mM EDTA, 0.5 mM DTT, 5% glycerol and 0.1% Triton X100 buffer, than filtered and centrifuged; subsequently the material was precipitated at different salt concentrations, dialyzed and further separated through ultrafiltration membrane. The samples from each step of this process were evaluated for the amount of protein, total polyphenols, protein profile characterization (SDS-PAGE) and antioxidant activity. Regarding protein characterization, foliar concentration obtained was 5.29 to 36.47 mg/mL. The protein profile by SDS-PAGE showed bands with a molecular weight between 3 and 188 kDa. As for analysis of total polyphenols, values from 0.125 to 0.338 mg GAE/mL were obtained. All samples had antioxidant activity, however, the isolate evaluation of those showed that much of this activity can be attributed to the protein-polyphenol compound present in Fraction III A. This sample had a protein band of approximately 10 kDa that when isolated continued to present a great antioxidant capacity.
Keywords: Ilex paraguariensis; Proteínas; Compostos bioativos; Atividade antioxidante; Proteins; Bioactive compounds; Antioxidant activity; ACCNPQ::Ciências da Saúde::Nutrição